The descent - Marshall, Neil.; Colson, Christian; Lions Gate Entertainment (Firm).; D'Concorde Recording Corporation (Santa Monica, Calif. Lionsgate; distributed in the Philippines by D'Concorde Recording Corporation, 2006)
On an annual extreme outdoor adventure, six women friends meet in a remote part of the Appalachians to explore a cave hidden deep int the woods. Far below the surface of the earth, disaster strikes when a rock fall blocks their exit and there is no way out. The women push on, praying for another exit, but there is something else lurking under the earth. The friends are now prey, forced to unleash their most primal instincts in an all-out war against an unspeakable horror that attacks without warning.
Director of photography, Sam McCurdy ; editor, Jon Harris ; music, David Julyan ; costume designer, Nancy Thompson ; production designer, Simon Bowles.
Shauna Macdonald, Natalie Mendoza, Alex Reid, Saskia Mulder, MyAnna Buring, Nora-Jane Noone, Oliver Milburn, Molly Kayll.
Unrated; for strong violence/gore and language.
VCD.
Keywords: Extreme environments -- Drama; Female friendship -- Drama; Self-preservation -- Drama